PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. DECORINDO INTI ALAM WOOD - Firdaus, Firdaus; Lestari, Niti; Mursanto, Mursanto; Purboyo, Purboyo (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2024)
This research aims to investigate the influence of leadership style and work discipline on employee performance at PT. Decorindo Inti Alam Wood. The research method used is quantitative. The population under study comprises all employees of PT. Decorindo Inti Alam Wood, totaling 250 individuals. Sampling was conducted using the Slovin formula calculation technique, resulting in 71 employees of PT. Decorindo Inti Alam Wood as respondents. The research findings indicate that, partially, leadership style significantly affects employee performance at PT. Decorindo Inti Alam Wood, confirming the first hypothesis. Similarly, work discipline partially significantly influences employee performance, confirming the second hypothesis. Furthermore, the research results demonstrate that, collectively, leadership style and work discipline simultaneously influence employee performance at PT. Decorindo Inti Alam Wood, confirming the third hypothesis. As a recommendation, the researcher suggests that PT. Decorindo Inti Alam Wood make improvements based on the research findings to enhance the quality of employee work and production, thereby achieving company goals and improving employee performance